Phase Identification of Dual-Phase (DP980) Steels by Electron Backscatter Diffraction and Nanoindentation Techniques. (19th January 2016) - Zhang, Fan; Ruimi, Annie; Field, David P.
Abstract: Phase identification of multi-phase materials provides essential information relating the material to its mechanical properties. In this study we selected DP980, a type of dual-phase steel, to investigate the content of martensite and ferrite grains. A combination of advanced techniques was used to provide detailed and precise information of the microstructure. Scanning and transmission electron microscopy were used to provide observations of the sample surface at different scales. Martensite and ferrite phases of DP980 were further identified and characterized using electron backscatter diffraction and scanning probe microscopy. Results obtained with nanoindentation tests confirmed that the differences in nanohardness values in single-phase grains are martensite and ferrite with different surface heights shown by scanning probe microscopy. The similarity shown in the image quality map and scanning probe microscopy proves that a large fraction of martensite can be distinguished in this undeformed material using image quality parameters obtained during electron backscatter diffraction imaging.